Limestone Quarry Waste Promotes the Growth of Two Native Woody Angiosperms - Hayyat, Muhammad Umar; Siddiq, Zafar; Mahmood, Rashid; Khan, Amin U.; Cao, Kun-Fang (Frontiers in Ecology and Evolution, 2021)
Limestone quarrying is one of the active mining practice which produces bulk of solid remains and also alters the habitat by the removal of plants, but the utilization of such waste for the growth of plants is not much investigated. The present study was planned to evaluate the effects of limestone quarry waste on the growth of two native plants. The objective was to analyze the physico-chemical properties of the mining waste soil and also to determine whether mitigation measures would be required for the habitat restoration of quarry site and the utility of this waste for plantation purposes. For which we selected the two species i.e, Acacia modesta and Adhatoda vasica from the same habitat of the quarry site. These plants were grown in different proportions of quarry waste and garden soil was used as control. The growth was assessed by recording the plant height, number of branches per plant, root and shoot length, and total biomass. We also analyzed nitrogen, phosphorus, potassium, sodium, calcium, and magnesium contents of root and shoot tissues of both the species. We found a significant increase in plant height (1.24-fold and 1.19-fold greater than controls for A. modesta and A. vasica, respectively). The differences in number branches were also found, root, shoot length and biomass was also found. A significant and positive relationship was found between the measured roots mineral concentrations and the total plant biomass across both the species. We conclude that 1) the mining solid waste had necessary minerals for the studied plants species and no amelioration would be required for restoration of such sites with the selected indigenous plants; 2) the query waste promoted the growth of selected species. The results of present study can be used for planning the habitat restoration in the limestone areas which would have lost the plant cover.